“There is nothing less free than the free market”. Liberal interventionism and anthropogenesis in the post-Fordist capitalism era - Canavera, Julien (Revista de Filosofía, 2022)
The purpose of the present text is to show, contrary to what both its detractors and advocates often claim, that neoliberalism, in its critique of Keynesianism and the welfare state, does not at all intend to redirect the laissez-faire promoted by the marginalists, although publicly it has no qualms about accommodating itself to neoclassical rhetoric. On the contrary, it is aware that the free market -for which it advocates- is something that must be instituted and protected against social inertia; and that this requires state interventionism to protect the order of competition, as well as an institutional fabric (school, press, culture, etc.) that contributes to the shaping of a subjectivity adapted to the highly evolutionary and uncertain nature of capitalist society.
Keywords: market; interventionism; anthropogenesis; capitalism; neoliberalism